Prevention of Possible Anesthesia Complications in Pediatric Ophthalmology (Herald of the National Children's Medical Center, 2025)
Ensuring adequacy and safety of anesthetic management in pediatric ophthalmology requires an individualized approach and a high level of monitoring, due to the anatomical and physiological characteristics of pediatric patients and specific risks, including the oculocardiac reflex. The latter is a potentially dangerous complication during interventions on the eyeball and requires effective prevention. Modern strategies, including multimodal analgesia and gentle sedation, help minimize risks and improve outcomes.
Keywords: Ophthalmic anesthesia; children; anesthesia complications; propofol; stress protection; oculocardiac reflex